Rancang Bangun Sistem Informasi Akademik Berbasis Web ( studi kasus: SMA Swasta Harapan I Medan ) - Haida Dafitri, Marina Elsera (Query: Journal of Information Systems, 2017)
Submission of academic information to students, parents / guardians conducted at private high school SMA Harapan I Medan are still very ineffective and efficient both in terms of delivery time and in terms of finance. This is because the academic delivery is still manual in oral, written or via phone or SMS one by one. The impact of the process is the slow process of delivering academic information and the amount of expenditure in the delivery of information. To overcome these problems, then the academic community wants to improve the delivery of academic information systems using computerized technology. The purpose of the change is by building a School of Academic Information System (SISFO) Web-based SCRUM model. The system is built to produce academic information such as value and achievement of students in web-based schools that can be utilized by the academic staff to make it easier in conveying academic information to students, parents / guardians. This system includes and through several aspects of functionality, reliability, efficiency, and usability. And the scrum model used in the design of this system has a framework for building, developing and managing an ever-changing product. Keywords: Information , Academic, Scrum Model, Web